A Media Celebrity and Persuasive Communication - Kamaruddin, Azlina (2017)
Fedtri smiled at himself as he watched the mindful mind recalling past memories. The memories around the 1990s, stole his attention at the time. The children who ran to play in front of his eyes, cheerfully laughed occasionally.He smiled again.